Industrial Training Report: Sabah State Library / Shahidatul Ain Idrus - Idrus, Shahidatul Ain (Faculty of Information Management, 2020)
Industrial training 1s compulsory for a final year bachelor student of Faculty of Information Management. The requirements are to be fulfil due to have a degree holder. I've choose Sabah State Library as my industrial training location. The duration of internship is 5 months starting from 1st August until 31st December 2019. Sabah State Library is a public library which has gained so much experience on serving community. Also, Sabah State Library are suitable for Information Management student to do their internship. This report consist of 4 chapter which are introduction, organizational information, industrial training activity and industrial training reflection. Chapter 3 and 4 are the highlight of this report which contain the daily activities, special project and the perspective towards the library.